2019
DOI: 10.3390/cancers11071017
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Hallmarks of the Serrated Pathway in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is a leading cause of cancer death worldwide. It includes different subtypes that differ in their clinical and prognostic features. In the past decade, in addition to the conventional adenoma-carcinoma model, an alternative multistep mechanism of carcinogenesis, namely the “serrated pathway”, has been described. Approximately, 15 to 30% of all CRCs arise from neoplastic serrated polyps, a heterogeneous group of lesions that are histologically classified into three morphologic categories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(136 citation statements)
references
References 187 publications
(262 reference statements)
5
127
0
4
Order By: Relevance
“…In our population the incidence of a BRAF-MT was 20.1 %, in rightsided CCs 29.3 % (▶ Fig. 2A), supporting this thesis and in accord- ance with previous data [14]. Next to BRAF-MT, age leads to a higher frequency of DNA-methylation, provoking the equal effect of epigenetic gene silencing [34,35].…”
Section: Clinical Parameterssupporting
confidence: 90%
See 2 more Smart Citations
“…In our population the incidence of a BRAF-MT was 20.1 %, in rightsided CCs 29.3 % (▶ Fig. 2A), supporting this thesis and in accord- ance with previous data [14]. Next to BRAF-MT, age leads to a higher frequency of DNA-methylation, provoking the equal effect of epigenetic gene silencing [34,35].…”
Section: Clinical Parameterssupporting
confidence: 90%
“…The PETACC-8 study reported a percentage of 38.9 % and the NO147 trial 50 % of right-sided cancers [21]. A potential reason for a higher incidence of right-sided CCs within increasing age and female gender may be that CCs develops via the serrated pathway and activating mutation (MT) of the BRAF gene preferentially on the right side of the colon [3,[13][14][15]. These lesions are prone to acquire CpG island methylations, which leads to gene silencing [13].…”
Section: Clinical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, comparing all the distal and proximal tumors showed differences in K m (ADP) but not in V max values (Figure 2A). A study including 57,847 patients showed proximal patients had better outcomes than those with distal CRC in several subgroups including stage II disease, patients aged >70 years and mucinous adenocarcinoma [61]. Inside the KRAS mutated group, proximal and distal tumors were compared to see the potential effect of cancer location on metabolic changes.…”
Section: Resultsmentioning
confidence: 99%
“…Tumors are widely distributed from the proximal region of the colon to the rectum and each location is associated with different tumor-intrinsic characteristics (5). Most of these tumors arise from benign lesions called polyps, which progressively acquire genetic and epigenetic modifications to form malignant tumors and metastases (3,4,6,7). These include deletions, amplifications, mutations or methylation of the promoter of certain genes such as APC, SMAD4, TP53, BRAF, MYC, KRAS, PTEN, or MLH1 (3,4,8).…”
Section: Introduction Colorectal Cancer-epidemiology Pathophysiologymentioning
confidence: 99%